Fiscal Restructuring in the Group of Seven Major Industrial Countries in the 1990's : Macroeconomic Effects - Bartolini, Leonardo (IMF Working Papers; Working Paper ;, 1995)
This paper studies the fiscal restructuring of the first half of the 1990s in the major industrial countries. It presents and calibrates a simple model of the labor market and integrates it into a multi-country macroeconomic model that takes into account the effects of distortionary taxes. It then uses the resulting framework to simulate the effects of recent and prospective changes in fiscal policies in the group of seven major industrial countries. The analysis suggests that in the long run the impact on output is likely to be positive in those countries that relied relatively more on expenditure cuts or indirect tax increases (such as Canada, France, Japan, and the United Kingdom), while the effect of the fiscal restructuring on output is estimated to be negative in those countries that relied primarily on labor and capital taxes (Germany, Italy, and the United States).